2018
DOI: 10.20452/pamw.4183
|View full text |Cite
|
Sign up to set email alerts
|

An increase in high‑density lipoprotein cholesterol concentration after initiation of insulin treatment is dose‑dependent in newly diagnosed type 1 diabetes. The results of the InLipoDiab1 study

Abstract: RESEARCH LETTER HDL cholesterol and insulin treatment in type 1 diabetes 69 diagnosed T1D (28 women and 50 men; mean age, 25.7 years [range, 21.6-30.0 years]), who participated in the Insulin Therapy and Lipoproteins Profile in Type 1 Diabetes Study (InLipoDiab1, NCT02 306 005). All patients were treated with intensive insulin therapy from the onset of the disease. The inclusion criteria for the study were as follows: age between 18 and 35 years, newly diagnosed T1D and initiation of insulin therapy, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Refs. [ 50 , 53 , 54 , 55 ] demonstrated that Apo AI levels can be significantly augmented in newly diagnosed DM1 subjects during the first twelve months of diagnosis, and the authors suggested that apo levels can work as markers of micro and macrovascular imbalance that are associated with the late DM1 complications.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [ 50 , 53 , 54 , 55 ] demonstrated that Apo AI levels can be significantly augmented in newly diagnosed DM1 subjects during the first twelve months of diagnosis, and the authors suggested that apo levels can work as markers of micro and macrovascular imbalance that are associated with the late DM1 complications.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] The same indication bias mechanism may also apply for the adverse metabolic profile associated with the use of insulin, because some of the previous studies did show beneficial metabolic effects of insulin on lipid profile, characterized of lower total and LDL cholesterol, lower triglycerides, and higher HDL cholesterol. 23,24 The study results had to be interpreted within the context of several limitations. First, the study had a cross-sectional design and hence does not allow any causal inference.…”
Section: Discussionmentioning
confidence: 99%
“…Current hypertension guidelines recommend the use of these drugs in patients with diabetes mellitus or the metabolic syndrome 20‐22 . The same indication bias mechanism may also apply for the adverse metabolic profile associated with the use of insulin, because some of the previous studies did show beneficial metabolic effects of insulin on lipid profile, characterized of lower total and LDL cholesterol, lower triglycerides, and higher HDL cholesterol 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…All patients were hospitalized, on average, for 7 days due to newly diagnosed T1DM. The patients were treated with intensive insulin therapy using insulin pens from the moment of diagnosis and underwent the same educational program as we described previously [ 14 ]. The daily dose of insulin (DDI) was defined as the requirement for insulin per kilogram of body weight per day.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there is a lack of data on the relationship between apo abnormalities at the time of T1DM diagnosis and the development of atherosclerotic cardiovascular disease and other complications in the future. Our previous observations showed that the initiation of insulin therapy in patients with newly diagnosed T1DM causes a significant increase in HDL-C level after 3 months of treatment, and this effect is dose-dependent [ 14 ]. Conflicting data exist regarding the level of apo AI in patients with T1DM.…”
Section: Introductionmentioning
confidence: 99%